Relación entre la memoria operativa y el cálculo mental con los números naturales en estudiantes del grado 8º del Instituto Técnico Mercedes Abrego de San José de Cúcuta. - Rosa Virginia Hernández; Freddy Lozada-Sánchez; Luis Fernando Mariño (Ecomatemático, 2014)
Throughout the twentieth century and the twenty-first in the field of mathematics, has been a stream of authors and scientists have been interested in the how and why of how the human brain; and even if the information within the mind is processed. For this reason; The following article aims to analyze the possible relationship between working memory corresponding to that proposed by Baddeley and Hitch (1974) model of memory and mental arithmetic with natural numbers eighth graders (8th) by applying a descriptive correlational methodology character quasi experimental based on an associative, constructivist theoretical approach with studies of working memory proposed by Baddely and Hitch (2003). The instrument used was the memory test battery of Employment, Pickering, Gathercole and Bouquets. Medium and a linearly significant relationship between mental arithmetic tasks and the phonological loop was found; also a good inclination to remember the digits and a lower proportion of pseudo words it shows.